The R(−)-Enantiomer of Efonidipine Blocks T-type but Not L-type Calcium Current in Guinea Pig Ventricular Myocardium - Hikaru Tanaka; Chisa Komikado; Hideaki Shimada; Kentaro Takeda; Iyuki Namekata; Toru Kawanishi; Koki Shigenobu (Elsevier, 2004)
In guinea pig ventricular cardiomyocytes, the R(−)-enantiomer of efonidipine concentration-dependently blocked T-type Ca2+ current with 85% inhibition at 1 μM. In contrast, R(−)-efonidipine (1 μM) had no effect on the L-type Ca2+ current and Ca2+ transient in cardiomyocytes and contractile force in papillary muscles. Thus, R(−)-efonidipine is a highly selective blocker of the T-type Ca2+ current in native myocardia. Keywords:: R(−)-efonidipine, T-type Ca2+ channel, cardiomyocyte